‘Everyone does Jewish in their own way’: Vernacular practices of intermarried Finnish Jewish women - Czimbalmos, Mercédesz (Approaching religion, 2020)
Shortly after the Civil Marriage Act took effect in 1917 and the constitutional right to freedom of religion was implemented by the Freedom of Religion Act in 1922, the number of intermarriages started to rise in the Finnish Jewish congregations, affecting both their customs, and the structure of their membership. Initially, intermarried members and their spouses faced rejection in their congregations; however, during the second half of the twenty-first century, the attitudes towards intermarriages and intermarried congregants have changed significantly. Today, a high number of intermarriages is one of the key defining characteristics of Finnish Jewish communities. This article will concentrate on the vernacular practices of intermarried women in the Jewish Community of Helsinki and Turku. The core material of this article consists of semi-structured ethnographic interviews conducted in 2019 and 2020 with members of the two Finnish Jewish communities. The women presented in this study often combine models from different traditions. Instead of abandoning Judaism altogether, they ‘do Judaism in their own way’ by creating and (re)-inventing traditions they find meaningful for themselves and for their families.